Consumption of whole grains, fruit and vegetables is not associated with indices of renal function in the population-based longitudinal Doetinchem study. Issue 5 (13th September 2017) - Herber-Gast, Gerrie-Cor M.; Boersma, Marijke; Verschuren, W. M. Monique; Stehouwer, Coen D. A.; Gansevoort, Ron T.; Bakker, Stephan J. L.; Spijkerman, Annemieke M. W.
Abstract: Emerging evidence suggests that diet and renal function are related. Little is known, however, about the association of consumption of whole grains, fruit and vegetables with urinary albumin:creatinine ratio (ACR) and changes in estimated glomerular filtration rate (eGFR). We investigated this in a population-based cohort aged 26–65 years. Data were from 3787 participants from the Doetinchem cohort study, who were examined ≥3 times, 5 years apart. Consumption of food groups was assessed at each round with a validated FFQ. GFR was estimated at each round from routinely measured cystatin C and creatinine using the Chronic Kidney Disease-Epidemiology (CKD-EPI) equation. ACR was measured at the last round. Generalised estimated equation models were performed to examine associations with changes in eGFR. Linear regression was used to examine associations with ACR. Adjustments were made for covariates related to lifestyle, biological factors and diet. Mean baseline eGFR was 104·5 (sd 13·7) and mean annual decline was −0·95 (sd 0·67) ml/min per 1·73 m 2 over a 15-year follow-up. A trend was observed towards slightly less annual decline in eGFR among those with higher consumption of whole grains ( P =0·06). This association, however, was attenuated and no longer significant in multivariate models ( P =0·29). Consumption of fruit and vegetables was not associated with changes in eGFR and urinary ACR. In conclusion, consumption of whole grains, fruit and vegetables is not associated with changes in eGFR and mean ACR. As this was the first longitudinal study into this association in the general population, and as results are only partially in line with related studies, further research is recommended.